2020
DOI: 10.1002/jhet.4167
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of novel 1,5‐benzodiazepinederivatives: Crystal structures, spectroscopic characterizations, Hirshfeld surface analyses, molecular docking studies,DFTcalculations, corrosion inhibition anticipation, and antibacterial activities

Abstract: A series of newly pyrazolo‐1,5‐benzodiazepine derivatives (5‐7) was performed and characterized by using 1H, 13C‐NMR spectroscopic measurements. The molecular and crystal structures of two compounds 2 and 7 have also been further examined by single‐crystal X‐ray crystallography showing that the alkyl groups are beard by sulfur atom and to pyrazolic nitrogen atom in position 2 and not in position 1 of the tricyclic compounds as described in the literature. In addition, through Hirshfeld surface analysis, molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Heterocyclic molecules play a very important role in life processes and are of major interest in the industrial development of dyes, pharmaceuticals, pesticides, and natural products (Saber et al, 2020;El Ghayati et al, 2021;Patra & Saxena, 2010). Therefore, scientists have devoted considerable effort to finding efficient synthetic methods for a wide variety of heterocyclic compounds (Yeh et al, 2014;Liaw et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Heterocyclic molecules play a very important role in life processes and are of major interest in the industrial development of dyes, pharmaceuticals, pesticides, and natural products (Saber et al, 2020;El Ghayati et al, 2021;Patra & Saxena, 2010). Therefore, scientists have devoted considerable effort to finding efficient synthetic methods for a wide variety of heterocyclic compounds (Yeh et al, 2014;Liaw et al, 2015).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The chemistry of heterocyclic compounds still receives increasing interest because of the therapeutic importance of most heterocyclic compounds, especially those with nitrogencontaining heterocycles, which are of great interest as potential bioactive molecules (Taia et al, 2020;Sebbar et al, 2016;El Ghayati et al, 2021;Dinakaran et al, 2012;Lahmidi et al, 2018;Hni et al, 2019). In this regard, pyrazolo [3,4-d]pyrimi-]pyrimidines are an important family of heterocyclic compounds, and their derivatives possess various pharmacological properties (Bakavoli et al, 2010;Severina et al, 2016), including their applications as anti-microbial (Holla et al, 2006;Bakavoli et al, 2010), anti-tumor (Kandeel et al, 2012), anti-inflammatory (El-Tombary, 2013), anti-oxidant (El-Mekabaty, 2015), anti-cancer (Gupta et al, 2008;Maher et al, 2019) and anti-convulsant (Severina et al, 2016) agents.…”
Section: Chemical Contextmentioning
confidence: 99%
“…[1][2][3][4] Among them, 1,5-bezodiazepines consisting of a benzene portion and a seven-member dinitrogen heteroatomic ring were regarded as prerogative motifs due to their surplus therapeutic function, such as antipsychotic, anticonvulsant, antiinflammatory and antimicrobial. [5][6][7][8] Recently, it has been confirmed that 1,5-benzodiazepines can unambiguously inhibit the HIV virus and various microbes. [9][10][11][12] The lactam ring also occupies an essential position in heterocyclic species, maintaining the antibacterial activity of certain compounds.…”
Section: Introductionmentioning
confidence: 99%